Preliminary Steps in Institutionalizing Multi-Stakeholders Platforms - Prakasa, Danang Yudha; Nabila, Astria Zahra; Surdiasis, Fransiskus; suparno, Riyadi; Trilaksono, Teddy (Indonesian Business Review, 2025)
Solving complex and multi-faceted social problems requires strong cooperation from various parties. In this regard, Production, Protection, and Inclusion (PPI) Compact social initiative has been introduced as a concrete step of fostering cooperation and collaboration between various stakeholders in order to reduce environmental challenges while promoting inclusive, productive and sustainable business practices in Tebo Regency, Jambi, Indonesia. To promote cooperation between diverse stakeholders, understanding local dynamics as well as mapping involved and interested parties are requisite. Building credibility and trust between parties, maintaining transparency, delegating tasks to intermediaries to ensure neutrality and fairness as well as advancing decision-making processes and effective communication are some of the preliminary steps which should be taken.